Strong prospective trends in the Arctic and future opportunities in logistics. (2nd July 2016) - Myllylä, Yrjö; Kaivo-oja, Jari; Juga, Jari
ABSTRACT: The geopolitical importance of the Arctic region is growing. Behind this growing importance are many trends and changes in the Arctic landscape. We call these trends as strong prospective trends (SPTs), which affect the development of clusters and logistics needs and provide new business opportunities in the Arctic region. In this paper, the authors identify SPTs in the Arctic landscape and assess their impact on development needs and the emerging business opportunities in logistics. The study is based on empirical material collected in SMARCTIC future workshops where experts identified the most important SPTs for the Arctic business environment and for emerging new business opportunities before 2030. The study draws on an extensive literature review and on focused expertise of the core research group who also performed a cross-impact analysis of the SPTs. According to the foresight analyses of the expert workshops and our research group analysis, the most important trends in the Arctic region can be associated with natural resources such as raw materials and energy as well as technologies for their utilization. Novel technologies such as digital technology and biotechnologies are important, too, but not in such a leading role as they typically are in industrialized regions.